1991
DOI: 10.1111/j.1399-0004.1991.tb03061.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term follow‐up in females with Ullrich‐Turner syndrome

Abstract: In accordance with Nielsen & Stradiot's protocol (1987), we report on the long‐term follow‐up in 50 adult females with Ullrich‐Turner syndrome. Attention is drawn mainly to social problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…These data suggest that respondents do not consider medical complications of Turner syndrome to impact their health image greatly. An alternative explanation may lie within the support group system itself, for previous investigators have identified the positive impact of Turner syndrome support groups and their beneficial effects on both knowledge and self-image (Nielsen & Stradiot 1987, Nielsen 1989, Pelz et al 1991. The rates of cardiac and renal complications in the population reported here are in general agreement with previous investigations (Lippe 1989).…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that respondents do not consider medical complications of Turner syndrome to impact their health image greatly. An alternative explanation may lie within the support group system itself, for previous investigators have identified the positive impact of Turner syndrome support groups and their beneficial effects on both knowledge and self-image (Nielsen & Stradiot 1987, Nielsen 1989, Pelz et al 1991. The rates of cardiac and renal complications in the population reported here are in general agreement with previous investigations (Lippe 1989).…”
Section: Discussionsupporting
confidence: 90%
“…Many attempts have been made to correlate the type of X chromosome anomaly such as totally missing chromosome X (45X), aberrations of chromosome X (partial deletions of short and long arms, isochromosomes) and various mosaicisms in group of Turner syndrome individuals with their clinical features (Kusiak et al , 2000, 2005). The classical abnormalities of Turner syndrome include many somatic anomalies, such as short stature, infantile external genitalia, webbed neck, cubitus valgus, low hairline, shield‐like chest, anomalies in the structure of some internal organs and others (Turner, 1938; Horowitz and Morishima, 1974; Palmer and Reichmann, 1976; Arulanantham et al , 1980; Jaspers and Witkop, 1980; Goldman et al , 1982; Hall and Gilchrist, 1990; Lippe, 1991; Pelz et al , 1991; Temtamy et al , 1992; Robinson and de la Chapelle, 1996; Lopez et al , 2002). Some oral abnormalities were also observed, such as malocclusion (Harju et al , 1989; Laine et al , 1992; Szilagyi et al , 2000), early development of permanent teeth (Filipsson et al , 1965), high‐arched palate (Horowitz and Morishima, 1974), small teeth (Townsend et al , 1984; Varrela et al , 1988; Mayhall et al , 1991; Mayhall and Alvesalo, 1992; Midtbo and Halse, 1994a,b; Townsend and Alvesalo, 1995; Kusiak et al , 2000; Szilagyi et al , 2000; Zilberman et al , 2000), crown hypoplasia (Lopez et al , 2002), abnormalities in intercuspal distance (Lopez et al , 2002) and abnormality of root morphology of mandibule were also observed (Varrela, 1990, 1992; Lopez et al , 2002; Kusiak et al , 2005).…”
Section: Introductionmentioning
confidence: 99%